2016
DOI: 10.1002/ecy.1588
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and the demographic strategies of coral morphologies

Abstract: Understanding species differences in demographic strategies is a fundamental goal of ecology. In scleractinian corals, colony morphology is tightly linked with many demographic traits, such as size-specific growth and morality. Here we test how well morphology predicts the colony size-fecundity relationship in eight species of broadcast-spawning corals. Variation in colony fecundity is greater among morphologies than between species with a similar morphology, demonstrating that colony morphology can be used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 55 publications
(100 reference statements)
2
78
0
Order By: Relevance
“…Additionally, while fragmentation is a source of partial mortality, it is also a mechanism for asexual reproduction where fragments reattach to the reef (Highsmith, ; Karlson, ), providing an alternative way to increase population size (Smith & Hughes, ; Tunnicliffe, ). Sexual reproductive output also tends to be higher in species with lower compactness (Álvarez‐Noriega et al, ).…”
Section: Morphological Traits Linked To Performance Function and Resmentioning
confidence: 99%
“…Additionally, while fragmentation is a source of partial mortality, it is also a mechanism for asexual reproduction where fragments reattach to the reef (Highsmith, ; Karlson, ), providing an alternative way to increase population size (Smith & Hughes, ; Tunnicliffe, ). Sexual reproductive output also tends to be higher in species with lower compactness (Álvarez‐Noriega et al, ).…”
Section: Morphological Traits Linked To Performance Function and Resmentioning
confidence: 99%
“…Reproductive investment takes into account the estimated number of oocytes produced per colony and their energy (carbon) content. We estimated reproductive investment and number of oocytes from regressions of reproductive investment vs. colony sizes and of number of oocytes vs. colony size in Alvarez-Noriega et al (2016) for the range of observed colony sizes, and we calculated the mean values for each proxy. Note that regressions were only available for eight out of the 11 species in this study, and that fecundity measurements were taken at the site but from different colonies than those in this study, because sampling for fecundity in corals is destructive (branches must be broken off of the colony) and such injuries can affect subsequent colony growth.…”
Section: Discussionmentioning
confidence: 99%
“…Coral cover on the reef crest was estimated using 10 by 10 m line intercept transects in 2011 at 40 AE 3.0% (mean AE SE). The colonies were followed through time, and photographed from above with a scale plate every year from 2009 to 2013 (Madin et al 2014, Alvarez-Noriega et al 2016, Dornelas et al 2017.…”
Section: Study Location and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Álvarez‐Noriega et al. () have found trade‐offs among species belonging to four functional groups (two species per group): Massive species have a higher colony fecundity but a smaller colony reproductive investment (i.e., total amount of carbon invested in all the eggs produced by one colony) than plating or digitate species. The implication of this trade‐off for larval settlement and recruitment is unknown, but potentially of importance because many species produce lecithotrophic larvae (i.e., they rely solely on maternal energy reserves).…”
Section: Review Of Functional Traits and Associated Assumptionsmentioning
confidence: 99%